PENGETAHUAN TENTANG PUBERTAS DALAM MENGHADAPI PERUBAHAN FISIK PADA REMAJA AWAL DI SD DUTA BAKTI YOGYAKARTA - Andina Vita Sutanto (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2021)
Reproductive health in adolescents needs attention, because through youth as the next generation to build the nation. Adolescence is a transitional period between childhood and adulthood. At that time, optimal growth and development occurs, primary and secondary sex characteristics arise, fertility is achieved and psychological and cognitive changes occur. Before adolescence, there is a period of transition or transition, called puberty. Puberty is the occurrence of biological changes that include morphology and physiology. This happens rapidly from childhood to adulthood, especially in reproductive capacity, namely changes in the genitals from the child to adult stage. The formulation of the problem in this study is How Knowledge About Puberty In Facing Physical Changes in Early Adolescents at Duta Bakti Elementary School Yogyakarta. The purpose of this study was to determine the relationship between the level of knowledge of early adolescents about puberty with attitudes towards physical changes. This type of research is qualitative with an analytical observational approach with a cross sectional design. The research population was all 6th grade students at SD Duta Bakti Yogyakarta as many as 98 students. The research sample amounted to 10 students with purposive sampling technique. Data analysis used qualitative analysis by analyzing the content of the discussion, with the independent variable being the level of knowledge about puberty and the dependent variable. The results showed that early adolescents' knowledge of puberty was good, this was indicated by adolescents' understanding of good puberty and their attitudes towards understanding and accepting positively the changes they experienced during the pubertal process. Keywords: Youth, Puberty